2020
DOI: 10.21037/atm-20-3301
|View full text |Cite
|
Sign up to set email alerts
|

Potential effectiveness and safety of antiviral agents in children with coronavirus disease 2019: a rapid review and meta-analysis

Abstract: Background: The COVID-19 outbreak presents a new, life-threatening disease. Our aim was to assess the potential effectiveness and safety of antiviral agents for COVID-19 in children. Methods: Electronic databases (MEDLINE, Embase, Web of Science, the Cochrane library, CBM, CNKI, and Wanfang Data) from their inception to March 31, 2020 were searched for randomized controlled trials (RCTs), clinical controlled trials and cohort studies of interventions with antiviral agents for children (less than 18 years of ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Furthermore, human SARS-CoV-2 at the whole-genome level is >95% identical to a bat coronavirus (RaTG13), the natural reservoir host for multiple coronaviruses ( Xia, 2020 ; Zhang et al., 2020 ; Zhou et al., 2020 ). Given the rapid appearance and spread of this virus, there is no current validated vaccine or SARS-CoV-2-specific targeting therapy that is clinically approved, although statins, heparin, and steroids look promising for lowering fatality rates, and antivirals likely reduce the duration of symptomatic disease presentation ( Alijotas-Reig et al., 2020 ; Beigel et al., 2020 ; Beun et al., 2020 ; Dashti-Khavidaki and Khalili, 2020 ; Fedson et al., 2020 ; Shi et al., 2020 ; Tang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, human SARS-CoV-2 at the whole-genome level is >95% identical to a bat coronavirus (RaTG13), the natural reservoir host for multiple coronaviruses ( Xia, 2020 ; Zhang et al., 2020 ; Zhou et al., 2020 ). Given the rapid appearance and spread of this virus, there is no current validated vaccine or SARS-CoV-2-specific targeting therapy that is clinically approved, although statins, heparin, and steroids look promising for lowering fatality rates, and antivirals likely reduce the duration of symptomatic disease presentation ( Alijotas-Reig et al., 2020 ; Beigel et al., 2020 ; Beun et al., 2020 ; Dashti-Khavidaki and Khalili, 2020 ; Fedson et al., 2020 ; Shi et al., 2020 ; Tang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, human SARS-CoV-2 at the whole genome level is >95% identical to a bat coronavirus (RaTG13), the natural reservoir host for multiple coronaviruses (1, 4,5). Given the rapid appearance and spread of this virus, there is no current validated vaccine or SARS-CoV-2specific targeting therapy clinically approved although statins, heparin, and steroids look promising for lowering fatality rates and antivirals likely reduce the duration of symptomatic disease presentation (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…A range of study designs was included across different systematic reviews; most of which included retrospective/prospective observational studies and case series/case reports. The target population was confirmed cases of COVID-19 patients and included children in three reviews 43 , 46 , 47 and adult patients in the remaining studies. None of the included reviews reported on pregnant women.…”
Section: Resultsmentioning
confidence: 99%
“…arbidol hydrochloride, 20 , 23 , 28 , 30 , 31 , 33 , 34 , 44 , 46 , 49 , 53 , 56 , 58 , 60 and favipiravir), 20 , 23 , 46 , 53 , 58 neuraminidase inhibitors (e.g. oseltamivir), 19 , 23 , 31 , 33 , 44 , 46 , 53 , 56 , 60 nucleoside analogues (e.g. ribavirin), 23 , 28 , 31 , 33 , 34 , 44 , 46 , 56 , 58 nucleotide analogues (e.g.…”
Section: Resultsmentioning
confidence: 99%